Interfacial reactions and structural properties of explosively welded titanium/copper plates. Issue 1 (February 2020) - Paul, H; Chulist, R; Miszczyk, M M; Cios, G; Galka, A; Skuza, W; Petrzak, P; Mania, I
Abstract: In this study, the effect of post-processing heat treatment on the interface morphology and kinetics of intermetallic phase growth in titanium/copper bimetallic sheets were analyzed using a scanning electron microscopy and mechanical testing. Ti/Cu composite was fabricated by explosive welding. Then, clads were subjected to the post-welded annealing at 973 K for times ranging between 15 min and 100h. In the as-bonded state, the interface shows a wavy character with a limited number of melted zones, which are mostly composed of phases that are not observed in the Ti-Cu equilibrium phase diagram. Short-term annealing is shown to transform non-equilibrium phases into equilibrium ones, such as TiCu4 and Ti3Cu4. For longer annealing times, the growth of four intermetallic sublayers (Ti2Cu, TiCu, Ti3Cu4, and TiCu4) distributed along the entire interface is detected. However, the growth kinetics of particular sublayers was different. Volume fraction estimation of intermetallic phases at annealing times under study revealed the largest thickness for TiCu and TiCu4 phases. The nano-hardness of intermetallic sublayers was found to drop with the Ti content.